Comparative analysis of serum and sebum concentration of super-bioavailable itraconazole 50 versus 65 mg in healthy adult volunteers - Dhoot, Dhiraj S.; Mahadkar, Namrata; Jain, Gaurav; Kesharwani, Prashant (International Journal of Research in Dermatology, 2022)
Super-bioavailable itraconazole (SBITZ) is a new form of itraconazole which overcomes the pharmacokinetic issues of conventional itraconazole (CITZ). Currently two strengths are approved globally for SBITZ; 50 mg and 65 mg which exhibit greater bioavailability than CITZ and widely prescribed in systemic mycosis and dermatophytosis. Though both the strengths have proven to be bioequivalent with CITZ 100 mg but difference was reported in achieving therapeutic concentration of ITZ in patients. Secondly, skin kinetics study in terms of sebum concentration is lacking for both the strengths.